2011
DOI: 10.1038/emboj.2011.350
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosomal organization of replication origins and meiotic recombination hotspots in fission yeast

Abstract: In Schizosaccharomyces pombe, DNA replication origins (ORIs) and meiotic recombination hotspots lack consensus sequences and show a bias towards mapping to large intergenic regions (IGRs). To explore whether this preference depended on underlying chromatin features, we have generated genome-wide nucleosome profiles during mitosis and meiosis. We have found that meiotic double-strand break sites (DSBs) colocalize with nucleosome-depleted regions (NDRs) and that large IGRs include clusters of NDRs that overlap w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
57
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 64 publications
11
57
0
1
Order By: Relevance
“…They are enriched in poly dA:dT elements in S. cerevisiae (Iyer and Struhl 1995;Zhang et al 2011b), whereas they are not in S. pombe (Lantermann et al 2010). In fact, the A + T content of these regions is lower than the intergenic average in S. pombe (de Castro et al 2012). Chromatin assembly experiments have shown that the in vivo positioning pattern at the 5 ′ end of genes of S. cerevisiae can be reconstituted in the presence of ATP-dependent trans-acting factors, suggesting that the DNA sequence would play a minor role in nucleosome positioning (Zhang et al 2011b).…”
Section: Wwwgenomeorgmentioning
confidence: 93%
See 1 more Smart Citation
“…They are enriched in poly dA:dT elements in S. cerevisiae (Iyer and Struhl 1995;Zhang et al 2011b), whereas they are not in S. pombe (Lantermann et al 2010). In fact, the A + T content of these regions is lower than the intergenic average in S. pombe (de Castro et al 2012). Chromatin assembly experiments have shown that the in vivo positioning pattern at the 5 ′ end of genes of S. cerevisiae can be reconstituted in the presence of ATP-dependent trans-acting factors, suggesting that the DNA sequence would play a minor role in nucleosome positioning (Zhang et al 2011b).…”
Section: Wwwgenomeorgmentioning
confidence: 93%
“…This precise positioning is essential to modulate the access of proteins to specific sites in the chromosomes to regulate transcription (Bai et al 2010;Koster et al 2015), replication initiation (Lipford and Bell 2001;Eaton et al 2010;Soriano et al 2014), and recombination (Pan et al 2011;de Castro et al 2012).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…In addition, most replication origins in Saccharomyces cerevisiae are also associated with NDRs (42), although some efficient origins lack NDRs (43). However, a recent study in Schizosaccharomyces pombe found that ORC binding and origins do not overlap with NDR (44). Interestingly, recent proteomic analyses in human cells have suggested that ORC preferentially binds nucleosomes with H3K9m3 or H3K27m3, and that this binding is even more effective in the presence of CpG methylation (45).…”
Section: -G)mentioning
confidence: 99%
“…The media used in this study included yeast extract medium with supplements (YES) and essential minimal medium (EMM), which were prepared as described previously (Forsburg and Rhind 2006) with the following modifications: YES was supplemented with 2 g complete dropout powder, while EMM was supplemented with 2 g dropout powder lacking leucine and uracil. Dropout stock powder was prepared by mixing 5 g adenine SO 4 with 2 g each of the remaining 19 amino acids and uracil.…”
Section: Methodsmentioning
confidence: 99%